A retrospective cohort study reporting rituximab treatment for 33 patients with immunobullous disease. (3rd December 2020) - Watson, Nicola; Carrozzo, Marco; Hampton, Philip
Abstract: Background: Autoimmune bullous disorders, encompassing pemphigus and pemphigoid diseases, are associated with significant morbidity and mortality. This is in part due to high cumulative doses of corticosteroids in combination with immunosuppressant agents used in traditional treatment regimes. Rituximab is an antiCD20 monoclonal antibody which can induce complete remission, but it is currently unlicensed in the UK and approved only after other treatments have failed. Methods: We report a retrospective cohort study of 33 patients with pemphigus and pemphigoid diseases treated with rituximab from a single tertiary centre from 2013 to 2019. Results: "Complete remission off therapy" was achieved by 27.3% (n = 9), and a further 27.3% (n = 9) had complete remission on minimal therapy. Twenty‐one per cent (n = 7) had "partial remission on minimal therapy"; 9.1% (n = 3) patients were in the "consolidation phase, " and 12.1% (n = 4) had a "relapse/flare." A steady reduction in prednisolone doses was observed post‐Rituximab infusion. Pre‐Rituximab the median dose of prednisolone was 20mg (range 10‐35, IQR 25), 15mg (range 9.5‐22.5, IQR 13) at 1 month, 9mg (range 5‐10, IQR 5) at 6 months, 4mg (range 0‐5mg, IQR 5) at 12 months and 0 (0‐4.35, IQR 4.25) at 18 months. Twelve per cent (n = 4) of patients had documented infusion reaction symptoms. Twelve per cent (n = 4) had later infective complications. Conclusion: This real clinic data adds to the evidence that Rituximab is a safe and effective treatment for both pemphigus and pemphigoid autoimmune blistering conditions. Significantly, we were able to demonstrate a substantial reduction in corticosteroid dosage in our cohort of patients following rituximab treatment.